An increased proportion of progesterone receptor A in peripheral B cells from women who ultimately underwent spontaneous preterm birth. (December 2022) - Campe, Kim-Norina Jutta; Redlich, Anke; Zenclussen, Ana Claudia; Busse, Mandy
Abstract: The enormous challenge in unraveling the etiology of preterm birth (PTB) is to understand the complex interactions between gestational hormones, the immune system and reproductive tissues. PTB can be divided into spontaneous PTB (sPTB) and medically-indicated PTB, e.g. due to preeclampsia (PE) or HELLP syndrome. Progesterone (P4), important for establishment and maintenance of pregnancy, exerts anti-inflammatory effects. The impact of P4 on B cells and its support of maintaining maternal-fetal tolerance is widely unexplored. Therefore, we aimed to determine whether B cells express the progesterone receptor (PR) and to dissect a possible role of PR+ B cells in PTB. We found enhanced IL-6, IL-21 and TNF-α concentrations in maternal plasma in patients with sPTB and PE/HELLP compared to term delivery (TD), accompanied by enhanced PR-A expression by CD19+ B cells. In a second phase of the study, we recruited patients with imminent PTB (iPTB) and controls. Samples were collected at hospital admission and to a later time point, then divided into iPTB patients who delivered preterm and patients whose PTB was prevented. Within the group of iPTB patients, we observed very clear differences: enhanced levels of pro-inflammatory cytokines and increased percentages of PR-A+CD19+ B cells were found in iPTB patients that delivered preterm compared to patients who did not deliver preterm. We conclude that PTB is associated with the activation of an inflammatory pathway leading to the induction of PR-A by B cells. This might further trigger inflammation, result in the break of maternal-fetal tolerance and induce delivery. Graphical Abstract: ga1 Highlights: B cells from pregnant women express the progesterone receptor A (PR-A). Upon admission, PTB patients did not differ from non-delivering iPTB women in cytokine or P4 levels or PR-A+ B cells. Enhanced inflammation and increased PR-A+CD19 + B cells in patients immediate before PTB delivery.